LANGUAGE LEARNING STRATEGY OF STUDENTS IN INTENSIVE ENGLISH LANGUAGE INSTITUTE (IELI) OF FLINDERS UNIVERSITY - Marina Marina (Englisia: Journal of Language, Education, and Humanities, 2017)
This study aims to examine the influence of gender and nationality on the use of language learning strategies. The population of this study was the students who enrolled and studied in IELI of Flinders University and 34 students became the convenience samples. Strategy Inventory for Language Learner (SILL) questionnaire version 7.0 developed by Oxford (1990) was used as the main instrument of the research. The data analysis in this research used quantitative approach with Cronbach’s α for measuring item reliability, descriptive statistics for demographic data and Independent-Samples T-test for gender differences, and analysis of variance (ANOVA) for nationality differences. The results showed that gender and nationality has had an insignificant effect in the use of language learning strategies.